Can GPS be used to detect deleterious progression in training volume among runners? - Nielsen, R. O.; Cederholm, P.; Buist, I.; Sorensen, H.; Lind, M.; Rasmussen, S. (The Journal of Strength and Conditioning Research, 2013)
There is a need to ascertain if an association exists between excessive progression in weekly volume and development of running-related injuries (RRI). The purpose of this study was to investigate if GPS can be used to detect deleterious progression in weekly training volume among 60 novice runners included in a 10-week prospective study. All participants used GPS to quantify training volume while running. In case of injury, participants attended a clinical examination. The 13 runners who sustained injuries during follow-up had a significantly higher weekly progression in total training volume in the week before the injury origin (86% [95% confidence interval: 12.9-159.9], p = 0.026) compared with other weeks. Although not significant, participants with injuries had an increase in weekly training volume of 31.6% compared with a 22.1% increase among the healthy participants. The error of the GPS measurements in open landscape, forest, and urban area of volume was <6.2%. To conclude, no clinically relevant measurement errors of the GPS devices were found for training volume. Based on this, GPS has a potential to detect errors in training volume, which may be associated with development of RRI. Based on the results from the current study, increases in weekly training progression may become deleterious at a weekly increase above 30%, which is more than the 10% rule currently used as a guideline for correct progression in weekly volume by runners and coaches. Still, no clear evidence for safe progression of weekly volume exists. But it seems likely that some individuals may tolerate weekly progressions around 20-25%, at least for a short period of time.